Kunst und Ontologie : Für Roman Ingarden zum 100. Geburtstag - Galewicz, Włodzimierz; Ströker, Elisabeth; Strozewski, Władysław (Elementa, 1994)
This collection of 12 essays at the 100th anniversary of Roman Ingarden is to show the actuality of the outstanding Polish representative of twentieth century philosophy. The authors take up Ingarden's main philosophical topics and, accordingly, deal with phenomenological and ontological problems on the various modes of givenness and existence in the wide range of real and intentional being, true and fictional existence, and they devote particular interest to Ingarden's conception of reality as well as to his aesthetics and theory of arts.